Contrasting Images of Two Women in Ananta Pramoedya Toer's - Arining Wibowo; Deni Hadiansah (ELITE Association Indonesia, 2023)
ABSTRACTThis paper aims to describe the contrasting images of two women in Pramoedya Ananta Toer's Roman Bumi Manusia, namely Nyai Ontosoroh and her daughter, Annelis. The description of the contradictory self-images of Nyai Ontosoroh and Annelis is interesting to discuss considering the differences in racial background, social class, education, and the relationship between these characters and Minke, which is the storyteller's point of view in this novel. This research on Roman Bumi Manusia by Pramoedya Ananta Toer uses a feminist literary criticism approach. Roman Bumi Manusia has been widely studied through a feminist approach by emphasizing the character of Nyai Ontosoroh as a figure with the qualities of a feminist, but fails to see that the character of Annelis is depicted as the exact opposite of her mother. Annelis' character is depicted through the ideal and normative female self-image, as the other who depends on her mother and Minke's character who later becomes her partner. Annelis is described as an inferior and bound character, a depiction of a woman's self-image that is very far from feminist qualities. Keywords: Bumi Manusia, Contradiction, Citra Perempuan, Nyai Ontosoroh, Annelis.